Ritual folklórico y representaciones colectivas. Modelo de análisis comunicacional - Antonio Muñoz Carrión (Estudios sobre las Culturas Contemporáneas)
An interesting analysis proposal of the folkloric ritual from a communications theory perspective, following the methodological line of formalism. The author conducts a thorough following of "Russian formalism" and explains its reformation by different trends in social thought, and its breaking away from ingenuous attitudes revealing the "hidden" relations underlying social phenomena, as is the case of the ritual and so many other cultural manifestations. The work constitutes a very interesting introduction to the anthropological perspective.